Impact of economic development on corruption in ASEAN countries : panel non-linear model - Tiang, Jan Haw; Jerome, Kueh; Rayenda, Khresna Brahmana; Yong, Sze Wei (Inderscience Enterprises Ltd., 2023)
This study examines the nexus between corruption and economic development of the Association of Southeast Asian Nations (ASEAN) countries based on the annual panel data of all 10 ASEAN countries covering the period from 1996 to 2019. Empirical evidence implies there is a significant quadratic and cubic relationships between economic development and control of corruption of ASEAN countries. Corruption decreases in a country as income increases, but it rises at a moderate level of income. Finally, the level of corruption can be effectively controlled when the country achieves a much higher level of income than the intermediate level. The establishment of an empirical study on the corruption-growth relationship in ASEAN can contribute to a continuum of research and raise awareness to building a better governance environment at all levels.